STUDYING THE RELATIONSHIP BETWEEN CONGENITAL AND DISABLING DISEASES AND COPING STRATEGIES - Sevastyanova U.Y., U.Yu (Modern Psychology, 2020)
The article analyzes the coping strategies of the behavior of people with acquired and congenital disabilities. A study of the phenomenology of coping behavior in adults with congenital and acquired disabling diseases showed the specifics of the choice of coping strategies, due to the perception of the disorder, the duration of the disorder, as well as personal (dispositional) and social factors. We can note that close relationships (social factor) can be a resource for coping with difficult life situations, including the disease. Significant differences in coping strategies in people with congenital and acquired diseases were revealed. The main differences in indicators in people with acquired and congenital disabilities are manifested in the rethinking of the situation and its productive solution.
Keywords: coping strategies, dyadic coping, congenital disorder, acquired disorder, disability.